Direito à saúde: entre o dever estatal e a participação privada - Pereira, Fabrícia Helena Linhares Coelho da Silva (2018)
The present study aims to investigate the characteristics of the Brazilian health model, the functions of the State in health services and how the private sector can participate in the public health system, in accordance with the provisions of the Federal Constitution of 1988. Initially, the study aimed at understanding the regulation granted by the Federal Constitution of 1988 to the Brazilian health model, being the legal framework established for qualitative analysis formulated. In this regard, it is pointed out that the Brazilian Public Health System (SUS) is the main resource to promote a sanitary model whose universal and equal access to measures and services related to health provision, protection and recovery are aimed at reducing disease risk factors. The research methodology used was both bibliographic and documentary, aiming to improve the ideas by gathering information about the topic aforementioned and addressing all of them from a critical point of view. It is also important to mention that, although the State performs several roles regarding health services, as it is the direct executor, buyer or service regulator, the more the health service is public and provided directly by the State through the SUS, the more contemplated are the constitutional determinations concerning the development of a universal and equal access to the health system. Therefore, when the State does not prioritize direct health care, Brazilians are served by private institutions that manage public health resources, with reduced power, benefiting dependency on private health providers, or, in the worst-case scenario, Brazilians are encouraged to migrate to popular health plans or with restricted coverage, dividing the provision of health, as an alternative to Brazilian Public Health System.